Anticipating social differentiation and unintended consequences in scaling initiatives using GenderUp, a method to support responsible scaling - McGuire, E.; Leeuwis, C.; Rietveld, A.M.; Teeken, B. (Elsevier, 2024)
CONTEXT A key strategy in progressing towards the Sustainable Development Goals (SDGs) is scaling innovations to improve livelihoods of marginalized populations globally. Consequently, there has been a heightened emphasis on Agriculture Research for Development (AR4D) innovation teams' ability to swiftly identify innovations that can be scaled for broad impact. However, insufficient attention has been paid to the equitable distribution of benefits among different demographic groups, leading to documented unintended consequences affecting some of the most marginalized communities. To effectively contribute to the SDGs and avoid harm to specific groups, AR4D innovation teams must conscientiously consider various dimensions of diversity, including gender and other relevant factors.